Faktor Pendukung Dan Faktor Penghambat Pelaksanaan Pendidikan Spiritual Dalam Tarekat Sammaniyah - Tri Mulia Pertiwi; Rengga Satria (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the supporting factors and inhibiting factors for the implementation of spiritual education in the Sammaniyah congregation at the Surau Engku Boncah in Taeh Baruah, Lima Puluh Kota. This study uses the type of ethnographic research as a qualitative research method Sources of research data are Mursyid at Surau Engku Boncah, and one of the students at Surau Engku Boncah. Data collection the techniques used in this study were observation, interviews, and documentation. The research data were tested for validity using source, technique, and time triangulation techniques. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the inhibiting factor for spiritual education in the Sammaniyah congregation at Surau Engku Boncah is that there are teachers who are ready to carry out their duties, and the Taeh Baruah community is already used to the Tarekat, while the inhibiting factor is an ideology which considers the Tarekat to be heretical teaching.